(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Anemia during pregnancy is a common health problem that may adversely affect maternal and fetal outcomes. In Tra Vinh, data on the prevalence of anemia and related factors among pregnant women remain limited. Objective: To determine the prevalence of anemia and associated factors among pregnant women attending Tra Vinh University Hospital. Subjects and methods: A descriptive cross-sectional study combined with retrospective data collection was conducted among 162 pregnant women attending Tra Vinh University Hospital from March 2024 to May 2025. Anemia was defined as hemoglobin concentration <11 g/dL according to the WHO criteria. Univariate analysis was used to examine crude associations between selected factors and anemia status. The results were presented as crude prevalence ratios, cPRs, with 95% confidence intervals and p-values. Results: The prevalence of anemia among pregnant women was 22.22%. Most cases were mild anemia, accounting for 83.33%, followed by moderate anemia at 16.67%; no severe anemia was recorded. The prevalence of anemia was higher among Khmer pregnant women than among Kinh pregnant women, with cPR = 2.02; 95% CI: 1.15–3.54; p = 0.015. Compared with the first trimester, the prevalence of anemia was higher in the second and third trimesters, with cPR = 4.02 and cPR = 3.51, respectively. Conclusion: The prevalence of anemia among pregnant women attending Tra Vinh University Hospital was 22.22%, predominantly mild anemia. In univariate analysis, ethnicity and gestational stage showed crude associations with anemia status.